Business and trade in Islam - M. H. Syed; Muhammad Moinuddin Khan (Pentagon Press, 2010)
Islam considers business and trade to be the best mode of earning. And, among the different types of trade, Halal business is recommended as the best by Islam. Money earned through hard work and fair means is full of benefits